Characteristics of Symbolic Meaning of Culinary as City Icons - Gasari, Ayu; Yenrizal, Yenrizal; Pebriana, Rina (Telangke:Jurnal Telangke Ilmu Komunikasi, 2024)
This research is motivated by the richness of Indonesian culinary culture, especially Bolu Cupu from Kayuagung, Ogan Komering Ilir Regency, which has not been widely recognized as a regional symbol. Along with the increasing trend of culinary tourism, Bolu Cupu has the potential to become a city icon that reflects the identity and local wisdom of the local community. The purpose of this study is to reveal the symbolic characteristics and meaning construction of Bolu Cupu as a city icon, as well as its role in the development of MSMEs and tourist attraction in Kayuagung. This research used a qualitative method with a descriptive approach, relying on direct observation and in-depth interviews with traditional leaders, business actors, and local communities. The findings show that Bolu Cupu not only has historical and philosophical value, but also becomes a symbol of cultural identity that is passed down from generation to generation, without being affected by modernization in the manufacturing process. The implications of this research show that cross-cultural communication and preservation strategies through cultural narratives can strengthen the existence of local culinary as a city identity. Therefore, it is recommended that the local government and tourism actors actively promote Bolu Cupu through various media and local events, and integrate it into the regional creative economy development strategy.